Company name fluency, investor recognition, and firm value - Green, T. Clifton; Jame, Russell (Journal of Financial Economics, 2013)
Research from psychology suggests that people evaluate fluent stimuli more favorably than similar information that is harder to process. Consistent with fluency affecting investment decisions, we find that companies with short, easy to pronounce names have higher breadth of ownership, greater share turnover, lower transaction price impacts, and higher valuation ratios. Corporate name changes increase fluency on average, and fluency-improving name changes are associated with increases in breadth of ownership, liquidity, and firm value. Name fluency also affects other investment decisions, with fluently named closed-end funds trading at smaller discounts and fluent mutual funds attracting greater fund flows.